Chitosan-insulin nano-formulations as critical modulators of inflammatory cytokines and Nrf-2 pathway to accelerate burn wound healing - Sharda, Deepinder; Ghosh, Sandip; Kaur, Pawandeep; Basu, Biswarup; Choudhury, Diptiman (Discover nano, 2023)
Burn injuries are characterized by prolonged inflammatory phases, neurovascular damage, and hypermetabolism, eventually causing improper tissue regeneration. Insulin has gained considerable attention in normal and diabetic wound healing, yet its role in burn wounds remains poorly understood. In this study, insulin-chitosan nano-formulations (ICNP) were synthesized using a simple and robust mechanism and characterized to monitor specific interactions between insulin and chitosan, and the particles measuring approximately 30 nm in size exhibited mild alterations in the amide I, II, and III bonds of the insulin protein along with impressive insulin loading efficiency of 88.725 ± 0.295% under physiological conditions, and significantly improved burn wound healing in vitro (HEKa cells) and in vivo (murine third-degree burn model). The underlying mechanism behind superior wound closure and tissue remodeling was attributed to significant early phase reduction of pro-inflammatory cytokine IL-6 levels in ICNP-treated mice, while anti-inflammatory cytokine IL-10 levels became markedly elevated, resulting in enhanced re-epithelialization and collagen deposition. Furthermore, treatment of ICNP was associated with unregulated expression of Nrf-2, a key regulator of oxidative stress and inflammation, indicating their molecular crosstalk. These findings highlight the potential of ICNP as a promising therapeutic formulation for burn wound healing, promoting wound closure by modulating inflammatory phases, making it a valuable candidate for further clinical development in burn care. Graphical Abstract